2011
DOI: 10.1159/000332224
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Infectious Complication and Its Risk Factors after Urological Procedures of the Upper Urinary Tract

Abstract: Background:Invasive upper urinary tract procedures such as retrograde pyelography (RP) or single (S-J) or double J (D-J) stenting are commonly performed to assess or treat ureteral strictures. Urinary tract infection (UTI) can result after such procedures, and prophylactic antimicrobial administration (PAA) may be necessary. This study investigated infectious complications and risk factors, focusing on PAA. Methods:We studied antimicrobial prevention in 353 upper urinary tract examinations or treatments. Proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…No findings in regard to the type of AMP for these cases has been reported, though many reports have noted that the most common causative bacterium was Escherichia coli , followed by Enterococcus species and Pseudomonas aeruginosa , thus antimicrobials targeting those bacteria should be selected, such as penicillins with BLIs, first‐ or second‐generation cephalosporins, aminoglycosides, or quinolones (EL, III; RG, B) …”
Section: Detailed Exposition 3: Transurethral Examination or Surgery mentioning
confidence: 99%
“…No findings in regard to the type of AMP for these cases has been reported, though many reports have noted that the most common causative bacterium was Escherichia coli , followed by Enterococcus species and Pseudomonas aeruginosa , thus antimicrobials targeting those bacteria should be selected, such as penicillins with BLIs, first‐ or second‐generation cephalosporins, aminoglycosides, or quinolones (EL, III; RG, B) …”
Section: Detailed Exposition 3: Transurethral Examination or Surgery mentioning
confidence: 99%
“…He examined 20.9% patients with preoperative bacteriuria, and 10.8% of these patients had infective complications (p=0.000). Matsumoto in his study also concluded the preoperative bacteriuria was a statistically significant risk factor for occurrence of infective complications following urologic procedures in the upper urinary tract (18). Blackmur in his analyses of risk factors for developing sepsis following ureteroscopic lithotripsy, which was done with 462 patients, published that 34 (7.4%) patients had sepsis and that positive preoperative findings of urine culture were associated with occurrence of postoperative urosepsis, although an adequate antibiotic preoperative therapy was applied (p<0.001) (15).…”
Section: Discussionmentioning
confidence: 92%
“…These include advanced age, diabetes, bladder dysfunction, indwelling catheter, calculi, ureterointestinal anastomosis, previous manipulation, and bacteriuria. 19,28,31,32 Cochran et al 31 demonstrated that in patients with risk factors, the risk of sepsis was 50% without prophylaxis compared to 9% when prophylaxis was given. They found no statistically significant difference in patients without risk factors, although this may have been due to the small sample size (n ¼ 24).…”
Section: Percutaneous Nephrostomy (Pcn)mentioning
confidence: 99%
“…32 The most common indication for transrectal biopsy is transrectal ultrasound (TRUS) prostate biopsy. The majority of infections occur within the first week following the procedure, and the most common organism isolated on urine and blood cultures is Escherichia coli.…”
Section: Percutaneous Biopsymentioning
confidence: 99%